Investigation of the Drift Characteristics of Air-Induction and Conventional Flat-Fan Nozzles - Lönhárd, Miklós; Pályi, Béla; Cseke, Botond; Szilágyi, Attila (GEORGIKON FOR AGRICULTURE, 2024)
Air intake nozzles have been used on field crop protection machines for decades. According to the marketing texts, compared to the traditional flat-fan nozzles that are still common today, "spray uniformity and efficiency are increased." Their main characteristic is that they form large droplets saturated with air bubbles during atomization, which have got many advantages. On the one hand, the tendency of the spray-drifting is less, and on the other hand, due to the air inclusions, they break up into smaller droplets on target surface, causing better coverage. According to the literature, these advantages are proven by a large number of measurements, mainly in the laboratory, but also in operating conditions. In the case of the latter, the work quality of the spraying operation is influenced by many factors at the same time, the combined effect of which often cannot be calculated in advance. In this study, we compared the spray drifting characteristics of traditional flat-fan nozzles and air intake nozzles. Our tests ended with surprising results in addition to certain operating characteristics.
Keywords: field sprayer; working quality; spray drift; deposition; efficienc